KARAKTERISTIK PASIEN SKIZOFRENIA - P. Girsang, Gerhad; G. Tarigan, Mawar; A. Pakpahan, Edwin (Jurnal Kedokteran Methodist, 2020)
Background : Schizophrenia is one of the rising disease in society these days. Generally, people have little knowledge about this disease, and that this disease can develop in every age and level of education. Therefore, research is needed to know any charactheristics in schizophrenia. Method: This study is a study using the literature study method or literature review. Data obtained from secondary data using documentation techniques. Data documentation is carried out based on journals related to research variables. Conclusion: Based on this literature review about the characteristics of schizophrenia which is, age, gender, marital status, education, and profession, it is found that male is more vulnerable to develop schizophrenia than female, and lower education is more vulnerable to develop schizophrenia. Marital status and profession have little part in the characteristics of schizophrenia.